Impacts of land use changes on leaf litter decomposition in tropical streams - Gabriela García; Javier Pérez; Richard M. Bennett-Vaz; Gabriel Araúz; Luz Boyero; Aydeé Cornejo (Global Ecology and Conservation)
Land use changes (e.g., urbanization and agriculture) impose multiple stressors on freshwater ecosystems. Understanding their impacts is critical to preserve these ecosystems and to implement mitigation strategies. Here, we evaluated the effects of different land use types associated with urbanisation and agricultural activities on leaf litter decomposition rates of Ficus insipida in a tropical catchment in Panama, through a field experiment conducted in streams of rainforest, urban and agricultural areas (RF, UA, and AA, respectively). Our results revealed a negative correlation between the percentage of agricultural land use in the catchment and decomposition rates. Although detritivore-mediated decomposition was generally low, detritivore diversity and abundance were higher in RF compared to UA and AA sites. Our findings underscore the need to preserve not only the riparian habitat, but to consider the whole catchment to maintain key ecosystem functions such as leaf litter decomposition and nutrient cycling, especially under escalating land use pressures.